PENYULUHAN PEMBUATAN MASKER ORGANIK BIJI COKLAT DI DUSUN LUBUK DALAM KECAMATAN TAMAN RAJO KABUPATEN MUARO JAMBI - Febriyenti, 0la; Juwita, Agnes; Fadila, Aulia; Nursaya'bani, Dimas Saad; Sari, Gusti Nurmila; Yuniansyah, Lutfhi Suci; Andriani, Lili; Wati, Misna; Siregar, Ulica Elidawati (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Facial masks are skincare cosmetics that have many advantages, namely to prevent premature aging, maintain facial skin, detoxify the skin, cure acne, and cleanse pores. Chocolate (Theobroma cacao L.) is one of the leading commodities in Indonesia. The content of flavonoid compounds has potential as an antioxidant. Antioxidants that can prevent the entry of free radicals that can interfere with the activity of enzymes other than that can prevent wrinkling and age on the skin. This activity carried out, starting from the preparation of the cocoa organic mask extension material, the collections of content, the implementation of the natural mask extension in Dusun Lubuk Dalam. The results of this activity are mothers who can make organic masks from cocoa beans that are beneficial for facial skin health. Lubuk Dalam is one of the villages in Kemingking Dalam Taman Rajo, Muaro Jambi, which has significant natural resources and has excellent potential for use as preparation material. Natural resources, namely chocolate fruit often found in this region. Therefore, a program is needed to improve public understanding and knowledge about the use of herbs for skin health and cosmetic preparation through counseling activities. Besides, this program can increase the economic value of many plants that grow in Dusun Lubuk Dalam.